Estudo comparativo entre frameworks Java para desenvolvimento de aplicações web: JSF 2.0, grails e spring web MVC - Franco, Rebeca Such Tobias (2011)
The Java platform is the most used for the development of corporate web applications. The market demands that the software has to be developed with the least time and cost as possible and with quality and for that, the use of frameworks has become essential, because they increase productivity, maximize reuse and reduce the possibility of errors. Currently, there are many web frameworks available for Java. This paper presents some concepts related to web development in Java and describes three major frameworks presently used for this purpose: JSF 2.0, Spring Web MVC and Grails. It also makes a comparison between these frameworks. Through the implementation of a prototype of a financial system, it’s possible to observe in practice the theoretical comparisons presented and define which framework has more advantages to the developer. It is concluded that Grails is the easiest to learn and the more simple to be used.